IIUM Green SEJAHTERA scorecard for mahallah - Zen, Irina Safitri; Zahari, Rustam Khairi; Mohamad Hanifa, Shamshina; Badron, Khairayu (2021)
A management tools and governance of IIUM Sustainable Ecosystem framework. Its function is to monitor the green initiative at the Mahallah level. Sustainable Ecosystem framework functions to interpret the sustainable ecosystem which is defined as the ecosystem consisting of water, energy, waste, spatial, land, physical structures, nature (trees, plants, animals) as part of the complex of living organisms, their physical environment, and all their interrelationships in a particular unit of space (Britannica Dictionary). The scorecard includes the Health and Wellbeing component which consider the Human as a part of the ecosystem. Hence, we rename it as IIUM Green Sejahtera Scorecard for Mahallah.